The Relevance of Integrated Reporting in Investment Decision Making: A Proposed Framework - Baser, Abdul Alim; Saleh, Zakiah; Abdullah, Mazni (Asian Journal of Accounting Perspectives, 2022)
Research aim: Although Integrated Reporting (IR) has been widely adopted worldwide, literature on its usefulness in stock investment decision making is still scant and inconclusive. As such, this paper aims to articulate a conceptual framework to catechize the nexus between IR information, and stock investment decision making. Design/ Methodology/ Approach: The extant literature on IR is critically reviewed to identify gaps in knowledge, and finally to propose a framework that can link the IR and investment decision making. Research finding: This paper argues that IR information disclosed through six types of capital information (Financial, Human, Intellectual, Manufactured, Natural, and Social and Relational) can impact stock investment decision making both directly and indirectly. The indirect or mediation effect is performed by the reporting engendered firm’s reputation as perceived by the investors. Theoretical contribution/ Originality: Bearing stockholders’ information needs, this paper broadens the demand-side IR literature by showing an otherwise overlooked interlinkage between IR information, and investment decision making. Practitioner/ Policy implication: This paper offers new insights to investors, regulators, and researchers who had been arguing and searching for the usefulness of IR in the capital market. Research limitation: Since IR is a growing field of research, future research might include different behavioural biases or personal values in the proposed investment decision making framework. Keywords: Integrated Reporting (IR), Investment decision, Corporate reputation, Corporate reporting. Type of article: Conceptual paper JEL Classification: M14, M40, M41, M48, G11, G38